Development and Validation of the Knowledge and Attitude Scale Toward COVID-19 Pandemic Breaking Transmission Chain (KA-C) Among Iranian Population - Abounoori, Mahdi; Maddah, Mohammad Moein; Sharif Nia, Hamid; Rahmatpour, Pardis; Khosravifar, Shaghayegh; SamadiKouchaksaraei, Mohammad; Khosravifar, Shahrzad (Frontiers in Public Health, 2021)
Objectives: We aimed to develop a scale and evaluate this scale's validity and reliability to measure factors affecting people's knowledge and attitudes toward the pandemic breaking transmission chain. Methods: This exploratory mixed-method study was carried out in two phases: (1) item generation using literature reviews and interviews and, (2) item reduction by psychometric assessments of the developed scale. The face, content, construct (exploratory and confirmatory factor analysis), convergent, and discriminant validity of the scale were assessed in the Iranian population (n = 500) from March to June 2020. The Composite Reliability (CR) and the internal consistency correlation coefficient were estimated. Results: The Knowledge and Attitude Scale Toward COVID-19 Pandemic Breaking Transmission Chain (KA-C) among the Iranian population included 18 items. Two factors with a whole variance of 66.05% were identified by exploratory factor analysis. Factors were labeled as “health literacy” and “home health empowerment.” The confirmatory factor analysis showed the goodness of fit. The CR of the scale for first and second factors were 0.965 and 0.833 receptively. The scale's internal consistency correlation coefficient was acceptable (Cronbach's alpha = 0.960 and 0.823, average interitem correlation = 0.643 and 0.635, McDonald's omega = 0.963 and 0.829, for the first and second factor, receptively). Conclusion: The KA-C scale can be exerted to screen the people's knowledge and attitude about the COVID-19 pandemic breaking the transmission chain as a valid and reliable scale for further policymaking, health care providers, and for a multi-dimensional psychosocial assessment of the pandemic period.